Metode Sayyid Quthb dalam menafsirkan ayat-ayat mengenai kepemilikan dan harta (pembacaan terhadap Tafsir Fî Zhilâl al-Qur'ân) - Mujiatun Ridawati; Muhamad Johari (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2019)
Revelation in the form of a holy book (al-Qur'an) is often addressed to all humans, regardless of their circumstances or mindsets. Thus, it is entirely conceivable and even necessary for the creation of numerous distinct interpretations. One straightforward and obvious conclusion from these varied readings is that humans have an unequal capacity to comprehend the essence of revelation. It can be argued that Sayyid Quthb's thoughts are difficult to comprehend unless one is willing to read them thoroughly and possesses adequate language skills. Sayyid Quthb employs the tafsr bi ar-ra'yi method, in which he defines property as